2016
DOI: 10.2147/ott.s113832
|View full text |Cite
|
Sign up to set email alerts
|

<sup>18</sup>F-fludrodeoxyglucose maximal standardized uptake value and metabolic tumor burden are associated with major chemotherapy-related tumor markers in NSCLC patients

Abstract: ObjectiveMetabolic activity and tumor burden are significant for prognosis and metastasis of non-small cell lung cancer (NSCLC), including maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG). Chemotherapy resistance is a great challenge for treating NSCLC patients and is also closely related with several biomarkers such as epidermal growth factor receptor (EGFR), p53, and excision repair cross-complementing group 1 protein (ERCC1). Our purpose was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…There were 5 studies (409 patients) which investigated associations between 18 F-FDG PET and expression of EGFR in lung cancer [ 13 , 34 , 38 , 42 , 44 ]. The reported correlation coefficients ranged from 0.04 to 0.83 ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were 5 studies (409 patients) which investigated associations between 18 F-FDG PET and expression of EGFR in lung cancer [ 13 , 34 , 38 , 42 , 44 ]. The reported correlation coefficients ranged from 0.04 to 0.83 ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, MTV and TLG could provide a more accurate prognostic value. In recent stuides, TLG was considered as a much better indicator than MTV in prognosis evaluation [17]. It is conceptual understandable that TLG gained favour.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also demonstrated that a high SUVmax was a significant predictive marker of poor chemotherapeutic response. The mechanism may be related to the overexpression of p53 in tumor cells, as a previous study confirmed the positive correlation between SUVmax and p53 expression [30], and p53 overexpression has been proved to be significantly correlated with chemotherapy resistance in lung cancer [31]. This may Accumulating evidence has demonstrated that systemic inflammation plays a key role in tumorigenesis, progression and metastasis [17].…”
Section: Discussionmentioning
confidence: 79%